Association of SBP and BMI with cognitive and structural brain phenotypes in UK Biobank. Issue 12 (December 2020) - Ferguson, Amy C.; Tank, Rachana; Lyall, Laura M.; Ward, Joey; Welsh, Paul; Celis-Morales, Carlos; McQueenie, Ross; Strawbridge, Rona J.; Mackay, Daniel F.; Pell, Jill P.; Smith, Daniel J.; Sattar, Naveed; et al.
Abstract : Objective: To test for associations between SBP and BMI, with domain-specific cognitive abilities and examine which brain structural phenotypes mediate those associations. Methods: Using cross-sectional UK Biobank data (final N = 28 412), we examined SBP/BMI vs. cognitive test scores of pairs-matching, matrix completion, trail making test A/B, digit symbol substitution, verbal–numerical reasoning, tower rearranging and simple reaction time. We adjusted for potential confounders of age, sex, deprivation, medication, apolipoprotein e4 genotype, smoking, population stratification and genotypic array. We tested for mediation via multiple structural brain imaging phenotypes and corrected for multiple testing with false discovery rate. Results: We found positive associations for higher BMI with worse reaction time, reasoning, tower rearranging and matrix completion tasks by 0.024–0.067 SDs per BMI SD (all P < 0.001). Higher SBP was associated with worse reasoning (0.034 SDs) and matrix completion scores (−0.024 SDs; both P < 0.001). Both BMI and SBP were associated with multiple brain structural metrics including total grey/white matter volumes, frontal lobe volumes, white matter tract integrity and white matter hyperintensity volumes: specific metrics mediated around one-third of the associations with cognition. Conclusion: Our findings add to the body of evidence that addressing cardiovascular risk factors may also preserve cognitive function, via specific aspects of brain structure. Abstract : Supplemental Digital Content is available in the text